Erythrocyte‐derived extracellular vesicles aggravate inflammation by promoting the proinflammatory macrophage phenotype through TLR4–MyD88–NF‐κB–MAPK pathway. Issue 4 (12th April 2022) - Gao, Yuhan; Jin, Haiqiang; Tan, Hui; Cai, Xiaodong; Sun, Yongan
Abstract: Transfusion of stored erythrocytes is associated with the increased risk of morbidity and mortality in critical infections, but the mechanism is incompletely understood. Previous studies have suggested that RBC‐derived extracellular vesicles (EVs) may be potential risk factors for the occurrence of transfusion‐related immunomodulation. The purpose of our study was to evaluate the effects of RBC‐derived EVs under inflammatory conditions and explore the underlying mechanisms. In vivo, the activity of EVs was evaluated in cecal ligation and puncture (CLP)‐induced sepsis. Our results showed that EVs significantly aggravated the inflammatory response to sepsis in serum and lung tissue by promoting the production of the proinflammatory factors tumor necrosis factor‐α (TNF‐α）‐interleukin‐6(IL‐6), and interleukin‐1β (IL‐1β) and reduced the survival rate of septic mice in vivo. Importantly, adoptive transfer of EVs‐pretreated bone marrow‐derived macrophages (BMDMs) obviously aggravated systemic proinflammatory factors in mice after CLP surgery. In vitro, the proinflammatory properties of EVs were shown to elevate TNF‐α, IL‐6, and IL‐1β levels in lipopolysaccharide (LPS)‐stimulated BMDMs. Moreover, EVs promoted LPS‐induced macrophage polarization into a proinflammatory phenotype. The underlying mechanism might involve EV‐mediated up‐regulation of TLR4–MyD88–NF‐κB–MAPK activity to favor macrophage cytokine production. Graphical Abstract: EVs aggravate inflammation by promoting the proinflammatory macrophage phenotype with upregulation of NF‐κB and MAPK activity to favor macrophage cytokine production.